PEMODELAN PERTUMBUHAN PENDUDUK KABUPATEN ASAHAN MENGGUNAKAN PERSAMAAN DIFERENSIAL MODEL EKSPONENSIAL DAN MAPE - Sisca Sri Dewi Saragih; Khofifa Romaito Siregar; Nayla Aiwina Putri (Smart Education, 2026)
Abstract: Population growth is an important factor in regional development planning because it affects the provision of public services and infrastructure. This study aims to model the population growth of Asahan Regency using an exponential differential equation and evaluate the accuracy of the resulting predictions. A descriptive quantitative approach was employed using population data from Asahan Regency for the period 2021–2025 obtained from the Central Bureau of Statistics (BPS). The analysis involved constructing several exponential growth models and assessing their predictive performance using the Mean Absolute Percentage Error (MAPE). The results indicate that Exponential Model IV is the most accurate model, with a MAPE value of 0.2646%. Based on this model, the population of Asahan Regency is projected to increase from 838,852 people in 2026 to 898,377 people in 2030. These findings demonstrate that the exponential differential equation model provides highly accurate short-term population forecasts and can be utilized as a reference for regional planning and policy formulation related to population growth. Keywords: population growth; exponential model; differential equation; population projection; MAPE. Abstrak: Pertumbuhan penduduk merupakan faktor penting dalam perencanaan pembangunan daerah karena memengaruhi kebutuhan layanan publik dan infrastruktur. Penelitian ini bertujuan memodelkan pertumbuhan penduduk Kabupaten Asahan menggunakan persamaan diferensial eksponensial serta mengevaluasi tingkat akurasi prediksinya. Penelitian menggunakan pendekatan kuantitatif deskriptif dengan data jumlah penduduk Kabupaten Asahan tahun 2021–2025 yang diperoleh dari Badan Pusat Statistik (BPS). Analisis dilakukan melalui pembentukan beberapa model pertumbuhan eksponensial dan pengujian akurasi menggunakan Mean Absolute Percentage Error (MAPE). Hasil penelitian menunjukkan bahwa Model Eksponensial IV merupakan model terbaik dengan nilai MAPE sebesar 0,2646%. Berdasarkan model tersebut, jumlah penduduk Kabupaten Asahan diproyeksikan meningkat dari 838.852 jiwa pada tahun 2026 menjadi 898.377 jiwa pada tahun 2030. Hasil penelitian menunjukkan bahwa model eksponensial memiliki tingkat akurasi yang sangat baik dan dapat digunakan untuk memproyeksikan pertumbuhan penduduk Kabupaten Asahan dalam jangka pendek.. Kata kunci: pertumbuhan penduduk; persamaan diferensial; model eksponensial; proyeksi penduduk; MAPE.